Construction and validation of a low cost paediatric pelvis phantom. Issue 108 (November 2018) - Mohammed Ali, Ali; Hogg, Peter; Johansen, Safora; England, Andrew
Abstract: Purpose: Imaging phantoms can be cost prohibitive, therefore a need exists to produce low cost alternatives which are fit for purpose. This paper describes the development and validation of a low cost paediatric pelvis phantom based on the anatomy of a 5-year-old child. Methods: Tissue equivalent materials representing paediatric bone (Plaster of Paris; PoP) and soft tissue (Poly methyl methacrylate; PMMA) were used. PMMA was machined to match the bony anatomy identified from a CT scan of a 5-year-old child and cavities were created for infusing the PoP. Phantom validation comprised physical and visual measures. Physical included CT density comparison between a CT scan of a 5-year old child and the phantom and Signal to Noise Ratio (SNR) comparative analysis of anteroposterior phantom X-ray images against a commercial anthropomorphic phantom. Visual analysis using a psychometric image quality scale (face validity). Results: CT density, the percentage difference between cortical bone, soft tissue and their equivalent tissue substitutes were −4.7 to −4.1% and −23.4%, respectively. For SNR, (mAs response) there was a strong positive correlation between the two phantoms (r > 0.95 for all kVps). For kVp response, there was a strong positive correlation between 1 and 8 mAs (r = 0.85), this then decreased as mAs increased (r = −0.21 at 20 mAs). Psychometric scale results produced a Cronbach's Alpha of almost 0.8. Conclusions: Physical and visual measures suggest our low-cost phantom has suitable anatomical characteristics for X-ray imaging. Our phantom could have utility in dose and image quality optimisation studies.